Need Analysis for Developing Course Book for English for Elementary School Students With Local-Content Values - Devinta Puspita Ratri; Ika Puspitasari (IJEE (Indonesian Journal of English Education), 2019)
ABSTRACTThe shifting of curriculum from School-based to curriculum of 2013 which has been regulated under the Government of the Republic of Indonesia’s Regulation number 32 year 2013 about the alteration of Government Regulation number 19 year 2005 about National Standard of Education has some consequences in several factors. One of them is on the elimination of English subject in elementary school. Meanwhile, English is still badly needed in elementary school level. As a result, English is still offered in elementary school level but not as a subject. Instead, it is offered as a compulsory extra curricular for students. However, there was problem in its implementation which was caused by the different materials taught while the test administered was the same. As the consequence, the target for achievement could not meet the Minimum Mastery Criterion. It is even worse thatEnglish score becomes one of the requirements for enrolling in Junior High level. Thus, uniformity of syllabus and teaching materials for English subject for elementary school students is deemed necessary. Local values needs also to be embedded in the teaching materials to be developed as it is important in providing character education and reinforcing nasionalism for students. Prior to material development, a guideline for development is required.  Thus, need analysis and local wisdom-based syllabus development for elementary school level becomes the focus for this research. ABSTRAKPerubahan kurikulum tingkat satuan pendidikan (KTSP) menjadi  kurikulum 2013 untuk tingkat sekolah dasar berkonsekuensi pada berbagai faktor. Salah satunya adalah penghapusan mata pelajaran Bahasa Inggris pada tingkat sekolah dasar. Sedangkan permintaan masyarakat masih besar terhadap pembelajaran Bahasa Inggris di tingkat sekolah dasar. Dengan kondisi seperti sekarang ini, Bahasa Inggris tetap diberikan di tingkat sekolah dasar bukan sebagai mata pelajaran namun sebagai ekstra kulikuler wajib. Pada pelaksanaannya, timbul masalah karena tidak adanya keseragaman materi yang diberikan pada siswa padahal Bahasa Inggris diujikan di ujian sekolah. Sehingga target pencapaian Bahasa Inggris tidak bisa memenuhi Kriteria Ketuntasan Minimal (KKM). Ironisnya lagi, nilai Bahasa Inggris adalah sebagai salah satu syarat untuk masuk Sekolah Menengah Pertama. Maka dari itu, perlu adanya keseragaman silabus dan buku ajar Bahasa Inggris untuk sekolah dasar. Kearifan lokal juga dimasukkan dalam pengembangan buku ajar Bahasa Inggris untuk menanamkan pendidikan karakter dan penguatan rasa nasionalisme bagi peserta didik. Sebelum mengembangkan buku ajar, perlu ada acuan sebagai dasar pengembangan. Maka, dalam penelitian ini, dilaksanakan analisa kebutuhan dan pengembangan silabus untuk buku ajar berbasis kearifan lokal untuk sekolah dasar. How to Cite: Sartika,  D. H. M., Santihastuti, A., Wahjuningsih, E. (2019). Need Analysis for Developing Course Book for English for Elementary School Students With Local-Content Values. IJEE (Indonesian Journal of English Education), 6(1), 1-9. doi:10.15408/ijee.v6i1.9908